Reduced tonic inhibition in striatal output neurons from Huntington mice due to loss of astrocytic GABA release through GAT-3 - Wójtowicz, Anna M. (Frontiers Media S.A., 2013)
The extracellular concentration of the two main neurotransmitters glutamate and GABA is low but not negligible which enables a number of tonic actions. The effects of ambient GABA vary in a region-, cell-type, and age-dependent manner and can serve as indicators of disease-related alterations. Here we explored the tonic inhibitory actions of GABA in Huntington's disease (HD). HD is a devastating neurodegenerative disorder caused by a mutation in the huntingtin gene. Whole cell patch clamp recordings from striatal output neurons (SONs) in slices from adult wild type mice and two mouse models of HD (Z_Q175_KI homozygotes or R6/2 heterozygotes) revealed an HD-related reduction of the GABA(A) receptor-mediated tonic chloride current (I(Tonic(GABA))) along with signs of reduced GABA(B) receptor-mediated presynaptic depression of synaptic GABA release. About half of I(Tonic(GABA)) depended on tetrodotoxin-sensitive synaptic GABA release, but the remaining current was still lower in HD. Both in WT and HD, I(Tonic(GABA)) was more prominent during the first 4 h after preparing the slices, when astrocytes but not neurons exhibited a transient depolarization. All further tests were performed within 1–4 h in vitro. Experiments with SNAP5114, a blocker of the astrocytic GABA transporter GAT-3, suggest that in WT but not HD GAT-3 operated in the releasing mode. Application of a transportable substrate for glutamate transporters (D-aspartate 0.1–1 mM) restored the non-synaptic GABA release in slices from HD mice. I(Tonic(GABA)) was also rescued by applying the hyperagonist gaboxadol (0.33 μM). The results lead to the hypothesis that lesion-induced astrocyte depolarization facilitates non-synaptic release of GABA through GAT-3. However, the capacity of depolarized astrocytes to provide GABA for tonic inhibition is strongly reduced in HD.